Fish Spawning Aggregations in the Southeast Florida Coral Reef Ecosystem Conservation Area: A Case Study Synthesis of User Reports, Literature, and Field Validation Efforts - Benjamin M. Binder; J. Christopher Taylor; Kurtis Gregg; Kevin M. Boswell (Frontiers in Marine Science, 2021)
The formation of fish spawning aggregations (FSAs) is an essential part of the life history of many economically important fish species; however, their status are often poorly described in the literature either due to their occurrence in remote locations, during seasons with unsafe ocean conditions, or because they move on space and time scales that are difficult to predict and validate. Even in areas that are relatively accessible and heavily fished, such as southeast Florida, regionally relevant information describing FSA dynamics is generally absent from the literature and unaccounted for in existing management plans. We propose that this can be attributed to the fact that information is often held by stakeholders or found in unpublished manuscripts and reports. These sources are not widely disseminated and are therefore difficult to locate and integrate into fisheries management decisions. In this paper, we present a case study demonstrating the value of regional data syntheses as a tool to improve management activities in southeast Florida. Specifically, we engaged with local stakeholders to collect reports of FSA occurrence, and used Web of Science queries to collate information describing the reproductive dynamics of locally occurring snapper and grouper species. Reports were combined with regional FSA literature and provided to managers as a support tool to anticipate FSA occurrence, and to guide policy development and future FSA research. Resource users identified 13 potential aggregations from five species, but Web of Science queries revealed a paucity of information. Echosounder, camera, and fisheries dependent surveys were then used to corroborate reportedly active cubera snapper (Lutjanus cyanopterus), hogfish (Lachnolaimus maximus), and gag grouper (Mycteroperca microlepis) aggregations. Variability in the spatiotemporal aspects of FSA occurrence make them difficult to study, but this may also explain how certain species have avoided detrimental impacts from aggregation fishing. These data represent a first step toward describing FSAs that have historically occurred in the Southeast Florida Coral Reef Ecosystem Conservation Area and can be used by managers to prioritize future research efforts focused on species or hotspots of multispecies activity along the northern extent of the Florida Reef Tract.